Endoscopic Endonasal Approach for a Suprasellar Craniopharyngioma - Zenonos, Georgios A.; Snyderman, Carl H.; Gardner, Paul A. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives The current video presents the nuances of an endoscopic endonasal approach to a suprasellar craniopharyngioma.Design The video analyzes the presentation, preoperative workup and imaging, surgical steps and technical nuances of the surgery, the clinical outcome, and follow-up imaging.Setting The patient was treated by a skull base team consisting of a neurosurgeon and an ENT surgeon, at a teaching academic institution.Participants The case refers to a 67-year-old man who presented with vision loss and headaches, and was found to have a suprasellar mass, with imaging characteristics consistent with a craniopharyngioma.Main Outcome Measures The main outcome measures consistent of the reversal of the patient symptoms (vision loss and headaches), the recurrence-free survival based on imaging, as well as the absence of any complications.Results The patient's vision improved after the surgery; at his last follow-up there was no evidence of recurrence on imaging.Conclusions The endoscopic endonasal approach is safe and effective in treating suprasellar craniopharyngiomas.The link to the video can be found at: https://youtu.be/p1VXbwnAWCo.
Keywords: craniopharyngioma; endoscopic endonasal; suprasellar; skull base team